PENERAPAN METODE WEBQUAL 4.0 UNTUK EVALUASI KUALITAS WEBSITE SONGKET PaSH - Ariandi, Muhamad; Damayanti, Nita Rosa; Perkasa, Lang Dimas (ISTEK WIDURI, 2025)
The Songket PaSH website is a Palembang-based MSME (Micro, Small, and Medium Enterprises) platform that offers a variety of traditional handcrafted products, such as songket fabric, jumputan, and Palembang batik. Since its implementation, the website administrators have not conducted an in-depth analysis of user experience and interaction quality—whether from users who complete transactions or those who only browse. To maintain sustainable business-to-business (B2B) relationships and prevent communication breakdowns, an evaluation of the Songket PaSH website’s quality is necessary. This study aims to evaluate the website’s quality using a descriptive quantitative method with the Webqual approach. The Webqual method includes three main variables: Usability, Information Quality, and Service Interaction Quality, which collectively provide a comprehensive overview of a website’s quality. The results indicate that all three aspects fall into the